Foehn winds influence surface ablation on Glaciar Perito Moreno, southern Patagonian icefield - Masahiro Minowa; Pedro Skvarca; Koji Fujita (Journal of Glaciology)
The southern Patagonian glaciers are known for having extremely high ablation rates. Foehn winds are one of the suspected causes, however, their influence on the annual ablation, their interannual variations, and their relationship with climate change is not well understood. We analysed the in-situ meteorological data from 2003–2020 recorded at Glaciar Perito Moreno. Daily temperature lapse rates varied substantially, from −7.8°C km−1 to 10.4°C km−1, due to foehn, fog, and katabatic winds. We find that, on average, foehn events occurred 1073 hours per year, and accounted for 20% of the annual surface ablation. This increase in surface ablation rates during foehn events occurs as a result of the enhanced sensible heat flux and net shortwave radiation. The downglacier-directed foehn winds warm the air mass over the glacier, but because of the high humidity of the foehn here, they often release latent heat by condensation. Variations in the Amundsen Sea Low influence foehn occurrence by modulating the westerly winds, which is related to the hemispherical ocean and atmospheric variability. Our results show that the local climate play an important role in the surface melting of Patagonian glaciers.